Functional assays to evaluate antibody-mediated responses against Shigella: a review - Boero, Elena; Vezzani, Giacomo; Micoli, Francesca; Pizza, Mariagrazia; Rossi, Omar (Frontiers in Cellular and Infection Microbiology, 2023)
Shigella is a major global health pathogen and the etiological agent of shigellosis, a diarrheal disease that primarily affects young children in low- and middle-income countries. Shigellosis is characterized by a complex, multistep pathogenesis during which bacteria use multiple invasion proteins to manipulate and invade the intestinal epithelium. Antibodies, especially against the O-antigen and some invasion proteins, play a protective role as titres against specific antigens inversely correlate with disease severity; however, the context of antibody action during pathogenesis remains to be elucidated, especially with Shigella being mostly an intracellular pathogen. In the absence of a correlate of protection, functional assays recapitulating salient moments of Shigella pathogenesis can improve our understanding of the role of protective antibodies in blocking infection and disease. The lack of an animal model to fully recapitulate human pathogenesis renders in vitro assays even more important as they are unique tools to build correlates of protection. This review aims to discuss in vitro assays to evaluate the functionality of anti-Shigella antibodies in polyclonal sera in light of the multistep and multifaced Shigella infection process. Indeed, measurement of antibody level alone may limit the evaluation of full vaccine potential. Serum bactericidal assay (SBA), and other functional assays such as opsonophagocytic killing assays (OPKA), and adhesion/invasion inhibition assays (AIA), are instead physiologically relevant and may provide important information regarding the role played by these effector mechanisms in protective immunity. Ultimately, the review aims at providing scientists in the field with new points of view regarding the significance of functional assays of choice which may be more representative of immune-mediated protection mechanisms.